Regional VS30 model for the St. Lawrence Lowlands, Eastern Canada. Issue 3 (2nd July 2016) - Nastev, Miroslav; Parent, Michel; Benoit, Nicolas; Ross, Martin; Howlett, Danielle
ABSTRACT: Shear-wave velocity of the top 30 m, VS30, is commonly used for prediction of the seismic site response. This paper presents development, validation and uncertainty assessment of a regional VS30 model based on a combination of simplified 3D geology and statistically representative velocity values. Results identify soft marine sediments in deep sedimentary basins as zones most susceptible to seismic shaking. Compared to the available urban-scale seismic zonation studies, the regional model showed a success rate of roughly 64% in predicting local site category. The standard deviation was in average 30% of the expected VS30 value.